2009
DOI: 10.1099/ijs.0.009258-0
|View full text |Cite
|
Sign up to set email alerts
|

Dickeya species relatedness and clade structure determined by comparison of recA sequences

Abstract: Using sequences from the recA locus, we have produced a phylogeny of 188 Dickeya strains from culture collections and identified species relatedness and subspecies clade structure within the genus. Of the six recognized species, Dickeya paradisiaca, D. chrysanthemi and D. zeae were discriminated with long branch lengths. The clade containing the D. paradisiaca type strain included just one additional strain, isolated from banana in Colombia. Strains isolated from Chrysanthemum and Parthenium species made up mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
101
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 14 publications
8
101
0
Order By: Relevance
“…Multi Locus Sequence Analysis underpinned that Dickeya constitutes a distinct genetic clade in the soft rot Enterobacteriaceae [2]. Dickeya species are broad host range phytopathogens which principal disease symptom is maceration of plant tissues due to pectinolytic activity [2], [3]. Strains affecting potato are mainly found in three Dickeya species, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multi Locus Sequence Analysis underpinned that Dickeya constitutes a distinct genetic clade in the soft rot Enterobacteriaceae [2]. Dickeya species are broad host range phytopathogens which principal disease symptom is maceration of plant tissues due to pectinolytic activity [2], [3]. Strains affecting potato are mainly found in three Dickeya species, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Erwinia chrysanthemi is known in potato production in some European countries for over 40 years and is associated with slow wilt and internal stem necrosis. These strains are now assigned to D. dianthicola [3], [5]. However, in the past few years a new Dickeya biovar 3 strain, tentatively named ‘ Dickeya solani ’, has emerged as a common major threat, in particular on seed potatoes [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…D. zeae is able to infect both monocotyledons and dicotyledons, while most other Dickeya species could only infect dicotyledons (Goto 1979;Hussain et al 2008;Sinha and Prasad 1977). Phylogenetic analysis of Dickeya species showed that D. zeae is most distinct from other species and contains more sequevars than others (Parkinson et al 2009). This genetic diversity may explain the wide distribution of D. zeae, and the diseases caused by this bacterial pathogen have been documented in many different regions and countries around the world (SabetOur curiosity on the host range determinants and pathogenic mechanisms of D. zeae has led to identification of zeamine and zeamine II, which are structurally similar polyketide molecules with potent antimicrobial activities (Wu et al 2010;Zhou et al 2011;Liao et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Several genomic regions, including PCR fragments obtained from rep-PCR profiles (Rico et al 2008), plasmidial sequences (Bereswill et al 1992;Barbé et al 2014) and draft whole genome sequences (Pritchard et al 2013), have been used for the development of specific identification tools for plant pathogenic enterobacteria. The recombinase A (recA) gene is a valuable marker for the major bacterial groups (Eisen, 1995) and for differentiating species in Erwinia and related genera (Waleron et al 2002;Young and Park 2007;Parkinson et al 2009;Wensing et al 2010). Despite the high degree of sequence conservation in the recA gene, the existing sequence polymorphism was useful for differentiating 19 species in Erwinia (Waleron et al 2002).…”
Section: Introductionmentioning
confidence: 99%